The role of Skorokhod space in the development of the econometric analysis of time series - Mccrorie, J.R. (Інститут математики НАН України, 2008)
This paper discusses the fundamental role played by the Skorokhod space, through its underpinning of functional central limit theory, in the development of the paradigm of unit roots and co-integration. This paradigm has fundamentally affected the way economists approach economic time series as was recognized by the award of the Nobel Memorial Prize in Economic Sciences to Robert F. Engle and Clive W.J. Granger in 2003. Here, we focus on how P.C.B. Phillips and others used the Skorokhod topology to establish a limiting distribution theory that underpinned and facilitated the development of methods of estimation and testing of single equations and systems of equations with possibly integrated regressors. This approach has spawned a large body of work that can be traced back to Skorokhod’s conception of fifty years ago. Much of this work is surprisingly confined to the econometrics literature.